Employment Pattern of Nursing Graduates of NEUST - Guillasper, Jean N. (JPAIR Institutional Research, 2013)
Employment among nurses is one of the most sensationalized problems in the Philippines nowadays. Oversupply of fresh graduates and undersupply of experienced nurses is evident. The study aimed to determine the employment pattern of nursing graduates of Nueva Ecija University of Science and Technology in terms of their profile, professional information, and employment information of graduates of the said Higher Education Institution. The descriptive method of research was used in this study with the questionnaire as the main tool for data gathering. The data gathered were statistically treated, analyzed and interpreted. The study revealed that out of 1,047 respondents, 429 or 40.97% were employed; 284 or 27.13%, unemployed; 192 or 18.34%, underemployed; 136 or 12.99 were nurse trainee/volunteer and 6 or 0.57% were self-employed. It can be concluded that majority of nursing graduates was working in line with their course/profession and only few worked in non-hospital setting.